2011
DOI: 10.1002/jcb.23113
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of complement proteins in cerebrospinal fluid from active multiple sclerosis patients

Abstract: Multiple sclerosis (MS) is a demyelinating disease of the central nervous system with complex immunopathogenesis. Using the 2-D DIGE technology, we separate CSF proteins from patients with active MS and control subjects. Three of the seven differential proteins identified were related with complement system, and the network analysis of the differential proteins revealed complement activation involvement in active MS. Complement C4b (gamma chain) was confirmed elevated by performing western blotting analysis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 39 publications
1
35
1
Order By: Relevance
“…In summary, our data do not support the finding of lower levels of fH in active MS reported by Li et al [2011]. The reasons for this are unclear but may relate to small sample numbers or the pooled analysis methodology employed by Li et al In contrast, we have demonstrated higher levels of both CSF and serum fH in progressive disease and an influx of systemic fH at times of breakdown of the blood-CSF barrier.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In summary, our data do not support the finding of lower levels of fH in active MS reported by Li et al [2011]. The reasons for this are unclear but may relate to small sample numbers or the pooled analysis methodology employed by Li et al In contrast, we have demonstrated higher levels of both CSF and serum fH in progressive disease and an influx of systemic fH at times of breakdown of the blood-CSF barrier.…”
contrasting
confidence: 99%
“…T he recent paper by Li et al [2011] published in this journal demonstrated altered expression of three complement proteins, including factor H (fH), in pooled cerebrospinal fluid (CSF) from 12 patients with active multiple sclerosis (MS) compared to 12 patients with other unspecified neurological diseases. This timely data adds to the growing evidence implicating complement in active disease.…”
mentioning
confidence: 99%
“…Another study has also found an increased expression of C3, as well as C4b (an active peptide generated by the cleavage of C4) in the CSF of patients with acute RRMS when compared to healthy controls [23]. Moreover, plasma C4a (a fragment resulting from cleavage of C4) levels were significantly elevated in patients with active RRMS when compared to both controls and patients with stable RRMS [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, quantifying factor H levels in CSF indicated no change during active disease but significantly raised levels in progressive MS [29]. However, Li et al have found a decrease in the expression of factor H in the CSF of RRMS patients with active disease when compared to controls [23]. …”
Section: Introductionmentioning
confidence: 99%
“…There is currently a need for MS biomarkers that can help with earlier diagnosis, prediction, and evaluation of disease progression, and for monitoring treatment response . Several studies have focused on finding such biomarkers by comparing the proteins expressed in CSF between MS patients and controls . For most of the discovery studies, however, a low number of samples are included, or relatively few proteins are identified and quantified .…”
Section: Introductionmentioning
confidence: 99%